2021
DOI: 10.1026/0932-4089/a000348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Situational Factors on Team Planning

Abstract: Abstract. Although there has long been consensus in team research that planning generally has a positive impact on performance, very little is known about how input factors (e. g., situational factors) affect the planning behavior of teams. In addition, the various dimensions of planning remain largely unexplored. In this study, we examine the effects of time pressure, task routine, and decision importance on team planning. We suggest that planning consists of four dimensions: exploration, strategic planning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This is in line with the assumption of Marks et al (2001) that different tasks require different amounts of transition/action phases, which are reflected in the rhythm of teamwork. Our findings are also consistent with previous studies showing that the occurrence of transition processes such as team planning is dependent on the characteristics of a task—for example, challenging goals, the importance of the task, or time pressure (Oldeweme et al, 2021; Smith et al, 1990). Future research should examine more closely which task characteristics influence a team’s rhythm.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the assumption of Marks et al (2001) that different tasks require different amounts of transition/action phases, which are reflected in the rhythm of teamwork. Our findings are also consistent with previous studies showing that the occurrence of transition processes such as team planning is dependent on the characteristics of a task—for example, challenging goals, the importance of the task, or time pressure (Oldeweme et al, 2021; Smith et al, 1990). Future research should examine more closely which task characteristics influence a team’s rhythm.…”
Section: Discussionsupporting
confidence: 92%
“…This enabled us to show that there is indeed a shared construct, as common characteristic of a team. The results from a recently conducted experimental study by Oldeweme et al (2021) provide additional evidence of validation. The authors used the long-form scale to examine the effects of situational factors on team planning in two policy-capturing studies with undergraduates and employees and demonstrated additional positive findings regarding reliability and factorial validity, as well as moderate factor correlations.…”
Section: Discussionmentioning
confidence: 76%